Natural Monopoly, Public Trust and Vested Interests: Case of Power Sector in Pakistan - Naheed Zia Khan (Policy Perspectives, 2014)
The advent of neo-liberalism in the last quarter of 20 th century was a landmark development in the modern history of economic activity. One of the major features of the neo-liberalist counter-revolution, as opposed to the Keynesian interventionist revolution, was privatization of public utilities which were globally operating as natural monopolies in the state sector. The biggest of the latter universally existed in the power sector. Notwithstanding the global wave of power sector reforms and persistent deficit of financial resources and public trust in the corresponding sector of Pakistan, reforms of GENCOs and privatization of DISCOs in the country remain an unfulfilled promise and a wishful thinking respectively. This paper looks into the factors justifying the privatization of state monopolies in the power sector world over and attempts to make a similar case for Pakistan, advocating a consistent, gradual and sustainable process of reforms to protect societal welfare, save on public resources and help boost up industrial production. It is argued that vested interests are having formidable strongholds in the power sector of Pakistan, while economic theory and universal empirical evidence no longer favor the monopoly in electricity generation and distribution. The findings of study lead to the conclusion that world of 21 st century is being led by enterprising investors with bags full of money and a preparedness to welcome risk wherever the niche exists in the market. It is recommended that tangibly concrete efforts should be made to build up the confidence of domestic and foreign investors in the profitability potential of large scale industry of Pakistan; specifically, power sector reforms ought to be the frontline item of public policy agenda, given the current state of affairs regarding electricity supply to domestic and commercial users.